Dielectric characterization at high temperature of iron doped potassium strontium niobate ceramic by impedance spectroscopy - de Lima, Caio Vinicius [UNESP]; Lima Nobre, Marcos Augusto [UNESP]; Lanfredi, Silvania [UNESP] (Trans Tech Publications, 2015)
Tetragonal Tungsten Bronze structure TTB-type structure has attracted interest by the high anisotropy of the crystal structure. The dielectric characterization of iron-doped niobate of TTB-type structure, with stoichiometry KSr2(Fe0. 25Nb4. 75)O15- δ, prepared by Modified Polyol Method was investigated. Nanocrystalline single phase powders were obtained after calcination of the precursor powder at 1150 °C for 10 hours in an oxygen atmosphere. The dielectric characterization was performed by impedance spectroscopy, from room temperature to 600 °C, in the frequency range of 5 Hz to 13 MHz. The permittivity values obtained for KSr2(Fe0. 25Nb4. 75)O15- δ showed superior to the permittivity values of the KSr2Nb5O15 host structure in all temperature range investigated. At room temperature, the permittivity values (2100) of KSr2(Fe0. 25Nb4. 75)O15- δ is two times the permittivity values of KSr2Nb5O15. The substitution of niobium cation by iron cation in the KSr2Nb5O15 host structure showed a suppression of the ferroelectric (P4bm) → paraelectric (P4/mbm) phase transition.
Keywords: Dielectric properties; Impedance spectroscopy; Niobate; Tetragonal tungsten bronze structure